Efikasi Beberapa Agens Hayati Terhadap Penekanan Pertumbuhan Pyricularia grisea Secara In Vitro - Shyntiya Ayu Lestari; Umi Kalsum; Evan Purnama Ramdan (Agrosains : Jurnal Penelitian Agronomi, 2021)
The demand for rice as an important food crop in Indonesia is still constrained by the attack of blast disease caused by Pyricularia grisea. Controlling using synthetic chemical pesticides has a negative impact on the environment so that the use of biological agents is an alternative option. This study aims to determine the effectiveness of several biological agents against the pathogen P. grisea that causes blast disease in rice plants in vitro. The study used a completely randomized design (CRD) with 6 levels of treatment and was repeated 3 times using the dooble culture method. The results of the study showed that the inhibition of P. grisea was the highest in the treatment of P. grisea × Trichoderma sp. and P. grisea × Gliocladium sp. namely 67.04% and 51.85% compared to other treatments. The P. polymyxa and P. fluorescence treatments showed low inhibition, namely 23.70% and 28.89%. Biological agents Trichoderma sp. and Gliocladium sp. able to inhibit the growth of the fungus P. grisea. Each biological agent has a different percentage of inhibition in that caused by the inhibitory mechanism of the biological agent.